1996
DOI: 10.1016/0925-4439(95)00122-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HMG-CoA reductase inhibitors on growth and differentiation of cultured rat skeletal muscle cells

Abstract: HMG-CoA reductase inhibitors have been associated with skeletal muscle myopathy, ranging from asymptomatic elevations of serum creatine kinase (CK) activity to rhabdomyolysis. In this study, we assessed the effects of addition of different concentrations of simvastatin and pravastatin on growth and differentiation of cultured primary rat skeletal muscle cells. Protein concentrations, CK activity and percentage CK-MM, which is a parameter for maturation, were determined. Effects were generally stronger if inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Therefore, the clinical use of statins may be characterized by the occurrence of adverse effects, such as rhabdomiolysis and peripheral neuropathy (Corsini et al, 1995;Phan et al, 1995;Veerkamp et al, 1996). On the contrary, manumycin is a specific FPTase inhibitor that does not affect the biosynthesis of end products of isoprenoid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the clinical use of statins may be characterized by the occurrence of adverse effects, such as rhabdomiolysis and peripheral neuropathy (Corsini et al, 1995;Phan et al, 1995;Veerkamp et al, 1996). On the contrary, manumycin is a specific FPTase inhibitor that does not affect the biosynthesis of end products of isoprenoid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies highlight properties of lovastatin that seem unrelated to cholesterol biosynthesis. For example, treatment of cells with the lovastatin analogue, simvastatin (more potent than lovastatin) resulted in regeneration of cultured rat skeletal muscle cells with a toxic effect on growth and differentiation, without influencing the cholesterol and phospholipid content of the cells (34). Inhibition of the HMG-CoA reductase also induces differentiation of human monocytic cells associated with growth retardation and expression of differentiation markers (35).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggested that the depletion of GGPP is the root cause of cell death induced by statins. In rat skeletal myoblasts, however, statins induce cell death and inhibit differentiation at low doses, which do not affect the synthesis of cholesterol, and the statin-induced effects are not abolished by mevalonate (Veerkamp et al, 1996). The mechanism of the effect of statins at low doses is still unclear.…”
Section: Introductionmentioning
confidence: 95%